El secreto de sus ojos [videorecording (DVD)] = Secret in their eyes - Campanella, Juan José; Darín, Ricardo, 1957-; Villamil, Soledad; Rago, Pablo, 1972-; Godino, Javier, 1978-; Francella, Guillermo, 1955-; Sacheri, Eduardo A. (Eduardo Alfredo), 1967- (Sony Pictures Home Entertainment, 2010)
A crime-thriller about judicial cover-ups and corruption in Argentina, told through flashbacks.